2022
DOI: 10.31234/osf.io/fzv43
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Harmless bodily pleasures are moralized because they are perceived as reducing self-control and cooperativeness

Abstract: Why do some people moralize overindulgence in inherently victimless bodily pleasures, such as gluttony, masturbation, drinking, or laziness, when these behaviors appear devoid of any harmful consequences to other people? We test the hypothesis that these moral judgements stem from perceptions that overindulgence alters people’s self-control, thus making them more likely to cheat in cooperative interactions. In an online experiment on 400 American adults, participants judged that a target who was caused to incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 78 publications
(107 reference statements)
0
9
0
Order By: Relevance
“…Immoderate indulgence in bodily pleasures and intoxicants, meanwhile, appears perceived as degrading people's self-control, thus threatening people's ability to resist temptations to cheat in cooperative interactions (e.g., temptations of adultery, free-riding, violence, or stinginess, Fitouchi et al, 2021, for a review). Supporting this idea, psychological evidence suggests that perceiving harmless bodily pleasures (e.g., gluttony, drinking, idleness, masturbation) as altering people's self-control and cooperativeness predicts the propensity to moralize those pleasures (Fitouchi et al, 2022b). This converges with previous evidence that people perceive individuals indulging in gluttony both as less self-controlled and less trustworthy; that people perceive alcohol and drug consumption as favoring uncooperative behaviors (e.g., violence, nastiness, adultery); and that moralizations of harmless indulgences in sexual pleasure are predicted by perceptions of probable harm, more robustly than by disgust or disgust sensitivity (Fitouchi et al, 2021, for a review).…”
Section: The Moralization Of Apparently Harmless Wrongsmentioning
confidence: 99%
“…Immoderate indulgence in bodily pleasures and intoxicants, meanwhile, appears perceived as degrading people's self-control, thus threatening people's ability to resist temptations to cheat in cooperative interactions (e.g., temptations of adultery, free-riding, violence, or stinginess, Fitouchi et al, 2021, for a review). Supporting this idea, psychological evidence suggests that perceiving harmless bodily pleasures (e.g., gluttony, drinking, idleness, masturbation) as altering people's self-control and cooperativeness predicts the propensity to moralize those pleasures (Fitouchi et al, 2022b). This converges with previous evidence that people perceive individuals indulging in gluttony both as less self-controlled and less trustworthy; that people perceive alcohol and drug consumption as favoring uncooperative behaviors (e.g., violence, nastiness, adultery); and that moralizations of harmless indulgences in sexual pleasure are predicted by perceptions of probable harm, more robustly than by disgust or disgust sensitivity (Fitouchi et al, 2021, for a review).…”
Section: The Moralization Of Apparently Harmless Wrongsmentioning
confidence: 99%
“…A significant share of people believes that pornography Grubbs et al, 2019), fatty and sugary foods (Ruddock & Hardman, 2017), and intoxicants (Edelstein et al, 2020;El Khoury et al, 2019) can be addictive, while experimental evidence suggests that people intuitively associate addiction with loss of selfcontrol (see Vonasch et al, 2017). In vignette studies, we found that participants judged individuals increasing their indulgence in bodily pleasures over several months (e.g., pornography, alcohol, fatty and sugary foods) as altering their trait-self-control as a result of this lifestyle change (Fitouchi, André, Baumard & Nettle, 2022). Surveying religious attitudes toward pleasure, Glucklich (2020, pp.…”
Section: Lay Theories Of Modifiers Of Trait-self-controlmentioning
confidence: 78%
“…In the General Social Survey, support for legal restrictions of pornography is associated with the belief that "sexual material lead people to commit rape" (Sherkat & Ellison, 1997). In two vignette studies (N > 1,100), we presented participants with a target led to increase their indulgence in bodily pleasures, such as gluttony and masturbation (Fitouchi, André, Baumard & Nettle, 2022). Participants judged that, as a result of this lifestyle change, the target had likely become more prone to uncooperative behaviors, such as refusing to help a friend, free-riding on colleagues' work, and cheating his partner if he had the chance .…”
Section: Moralizations Of Bodily Pleasures Should Be Most Robustly As...mentioning
confidence: 99%
See 2 more Smart Citations